Simulation of overburden pressure during laboratory investigations of axial pipe–soil interaction - Sheil, B; Martin, C; Byrne, B (Thomas Telford, 2019)
The simulation of additional soil overburden pressure through the use of a surcharge system is a technique commonly adopted in laboratory testing of pipe–soil interaction. This paper examines the influence of surcharge boundary conditions and pressure level on the axial sliding behaviour of a trenched pipeline surrounded by sand backfill. A novel testing tank is employed in conjunction with a pressure bag system to simulate overburden pressure; both flexible and rigid surcharge boundary conditions are considered. Cyclic axial displacements are applied to a heavy pipe buried in a narrow trench, using two different sand backfills. The test pipe is instrumented to measure (a) the axial soil resistance developed on an isolated central section of pipe (thus avoiding tank boundary effects), and (b) the normal and shear contact stresses at a number of points around the pipe circumference. The results show that the type of surcharge boundary condition (flexible or rigid) has a significant influence on laboratory measurements of both the axial resistance and circumferential pressure distribution of a buried pipe section. Application and subsequent reduction of surcharge pressure is also shown to produce ‘locked in’ normal stresses on the pipe, thereby increasing the axial resistance. The results show that careful treatment of the surcharge boundary conditions and the surcharge pressure history are required to avoid inaccurate predictions of field behaviour.